Gender Analysis In Ulama Cadre Regeneration Education At UIN Antasari: A Review Of The Harmos Model - Huda, Nuril; Dahlliana, Difi (JHSS (JOURNAL OF HUMANITIES AND SOCIAL STUDIES), 2024)
Ulama education has a strategic role in forming religious leaders who not only master religious knowledge but are also able to respond to the development of the times. The Special Ulama Program (PKU) at UIN Antasari Banjarmasin is one of the efforts to regenerate ulama, but the aspect of gender equality in its implementation is still rarely studied. This study aims to analyze gender equality in PKU using the Harmos gender analysis model which includes aspects of access, participation, control, and benefits. The research method used is qualitative with data collection techniques through interviews, observations, and documentation. The results show that although formal access to the program is open to men and women, there are still disparities in participation and control. Men are more dominant in academic and religious leadership roles, while women tend to be limited to the education sector. Structural and cultural barriers are the main factors that influence these differences. Therefore, affirmative policies and leadership training are needed for women so that they can contribute more widely to the world of ulama. This research contributes to gender studies in Islamic education and provides recommendations for the development of a more inclusive and gender-responsive ulama education program.